Bone repair induced by different bone graft substitutes in critical-sized defects in rat calvaria - Aroni, Mauricio Andrés Tinajero (2019)
AbstractIntroduction The use of bone substitutes in grafting procedures as an alternative of the use of autogenous bone graft has been indicated, however, the direct comparison between these biomaterials has been little explored.Objective To evaluate the effect of different osteoconductive bone substitutes on the bone repair in critical-sized defects (CSDs) in rat calvaria.Material and method One CSD with an 8 mm diameter was made in each of the 40 rats used in this study. The animals were randomly allocated into 5 groups (n=8), according to the type of bone substitute used to fill the CSD: COA (Coagulum); AUT (autogenous bone); DBB (deproteinized bovine bone graft); HA/TCP (biphasic ceramic composed of hydroxyapatite and β-phosphate tricalcium); and TCP (β-phosphate tricalcium). A microtomographic analysis was performed to evaluate the remaining defect linear length (DLL) of the CSD and the volume of the mineralized tissues (MT) within the CSD at 3, 7, 15 and 30 days after the surgical procedure. In addition, a histometric analysis was performed to evaluate the composition of the repaired bone tissue (% Bone and % Biomaterial) at the 30-day period.Result It was shown that the COA had the lowest DLL and MT within the CSD. In addition, the COA presented the highest % of bone in CSD. The DBB had a higher MT and a higher % of bone substitute particles in the CSD than the AUT and TCP groups. The DBB and AUT groups presented higher % of bone in the CSD than the TCP group.Conclusion The use of the DBB promoted a better pattern of bone volume gain and formation compared to TCP and HA / TCP but was biologically inferior to the AUT.